Qualidade do tomate afetada pelo número de ramos por planta e pela poda apical - OLIVEIRA, VALTER RODRIGUES; FONTES, PAULO CESAR RESENDE; CAMPOS, JOANÊS PELÚZIO DE; REIS, FERNANDO PINHEIRO (Revista Ceres, 2015)
.